2020
DOI: 10.1590/1980-265x-tce-2018-0239
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Support Provided to Women During Childbirth by Companions in Public Maternity Hospitals

Abstract: Objective: to identify the factors associated with providing emotional, physical, informational and intermediation support for companions during childbirth. Method: this is a cross-sectional study, whose sample consisted of 861 companions from public maternity hospitals in Florianópolis, SC. Data collection was carried out from March/2015 to May/2016, using a questionnaire as a data collection instrument. The data were analyzed by Binary Logistic Regression, using the Hierarchical Model of Multivariate Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…A study performed in public maternity hospitals in Florianópolis, Brazil, detected an association between education and emotional and physical support, showing that the level of education favors companions to seek information to support their actions and are prone to request further clarification when needed. 12 Puerperal women whose companions attended at least one prenatal consultation were more likely to perceive the support received as adequate. These findings corroborate those found in a study performed in the Northeast region of Brazil, which found that the presence of a partner in prenatal consultations influenced positively the satisfaction of postpartum women regarding the support received during labor and delivery, especially when the partner completed a training on labor support.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A study performed in public maternity hospitals in Florianópolis, Brazil, detected an association between education and emotional and physical support, showing that the level of education favors companions to seek information to support their actions and are prone to request further clarification when needed. 12 Puerperal women whose companions attended at least one prenatal consultation were more likely to perceive the support received as adequate. These findings corroborate those found in a study performed in the Northeast region of Brazil, which found that the presence of a partner in prenatal consultations influenced positively the satisfaction of postpartum women regarding the support received during labor and delivery, especially when the partner completed a training on labor support.…”
Section: Discussionmentioning
confidence: 98%
“…There was no significant association between companions' level of education and the outcome, but the frequency of participants satisfied with the support received was higher among those whose companions had more than 9 years of education. A study performed in public maternity hospitals in Florianópolis, Brazil, detected an association between education and emotional and physical support, showing that the level of education favors companions to seek information to support their actions and are prone to request further clarification when needed 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is timely to identify their needs, expectations, and demands in order to support the development of educational actions and institutional strategies for empowerment, humanization, and qualified care. In particular, since there is a need to involve men in prenatal care (5)(6)(7)(8) , the present study opens up the possibility of presenting the implementation of good professional practices based on the guidelines provided by ministerial policies. Therefore, the aim of this study is to understand men's perceptions of their involvement during pregnancy.…”
Section: Introductionmentioning
confidence: 99%